1995
DOI: 10.1111/j.1365-3016.1995.tb00167.x
|View full text |Cite
|
Sign up to set email alerts
|

Preterm birth and low birthweight among children of Swedish and immigrant women between 1978 and 1990

Abstract: The aim of the study was to estimate the occurrence of low birthweight (LBW) and preterm birth among immigrant and Swedish women in Sweden. Eligible for analysis were all 1,270,407 singleton births in Sweden between 1978 and 1990 to mothers aged between 15 and 44 years, whose own country of birth was known. The mothers of the children were born in Sweden (88.2%), or had immigrated from Finland (4.4%), other Scandinavian countries (1.2%), Western Europe or North America (1.3%), Eastern Europe (1.8%), the Middle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
22
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 8 publications
6
22
0
4
Order By: Relevance
“…Previous studies in our study area have shown that the populations of non-Nordic origin tend to live in more polluted areas (Chaix et al 2006; Stroh et al 2005). The effect of country of origin on the risk of having a baby with reduced birth weight is well known (Moore et al 2009; Rasmussen et al 1995; Zeka et al 2008) and has also been demonstrated in Malmö, the largest city in Scania (Dejin-Karlsson and Östergren 2004). In the previous Malmö study, the main explanation did not seem to be maternal physical size, but rather maternal psychosocial factors such as low social anchorage (Dejin-Karlsson and Östergren 2004).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies in our study area have shown that the populations of non-Nordic origin tend to live in more polluted areas (Chaix et al 2006; Stroh et al 2005). The effect of country of origin on the risk of having a baby with reduced birth weight is well known (Moore et al 2009; Rasmussen et al 1995; Zeka et al 2008) and has also been demonstrated in Malmö, the largest city in Scania (Dejin-Karlsson and Östergren 2004). In the previous Malmö study, the main explanation did not seem to be maternal physical size, but rather maternal psychosocial factors such as low social anchorage (Dejin-Karlsson and Östergren 2004).…”
Section: Discussionmentioning
confidence: 95%
“…We used linear regression models for birth weight as a continuous outcome variable with both unadjusted and adjusted analyses. Recent studies have suggested that maternal country of origin is an important confounder (Moore et al 2009; Rasmussen et al 1995; Zeka et al 2008). In our study there was a strong correlation between parity and country of origin (distribution percentage for parity: in the Swedish population, parity 1, 51%; parity 2, 34%; parity ≥ 3, 16%; for any other country group within Sweden, 26%, 23%, and 51%, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, ethnic groups differ according to generational status, with US-born Hispanic and Asian women more likely to be first or second generation than US-born black or white women, who are mostly fourth or higher generation 98. Even first-generation migrants may differ in their risk of adverse birth outcomes according to their length of residence in the receiving country, information that was rarely collected 16 65 88…”
Section: Discussionmentioning
confidence: 99%
“…Asia was subdivided into south-central Asia (mainly India, Pakistan and Bangladesh) and east/south-east Asia, because women from the Indian subcontinent may differ in the risk of adverse birth outcomes compared with the rest of Asia 91. In the same vein, north Africans were separated from the rest of Africa (ie, sub-Saharan Africa) because of their particularly good birth outcomes,87 and were grouped with Middle Eastern countries, because some studies15 88 have grouped these regions together. Sensitivity analyses performed without these two studies did not affect the results regarding north Africans and therefore we did not exclude them.…”
Section: Methodsmentioning
confidence: 99%
“…In Switzerland, despite the large proportion of persons of foreign origin, (now almost 28 % of the population (Wanner 2004)), causes for the poorer reproductive health of selected migrant groups have not been elucidated, and no information is available on the antenatal care they receive (Bollini and Wanner 2006). In contrast, in other European countries, issues concerning maternal and child health status of foreign communities are more closely monitored (Oldenburg et al 1997;Rasmussen et al 1995;Stoltenberg & Magnus 1995;van Enk et al 1998;Balarajan & Botting 1989) Recently, problems of access to care have been identifi ed especially for illegal migrants in Switzerland (Achermann & Chimienti, in press), and the responsibility for lowering cultural and linguistic barriers for pregnant women has been addressed by a large non-governmental organization, the International Association for Maternal and Neonatal Health, as well as by several groups in large towns and hospitals (International Association for Maternal and Neonatal Health IAMANEH 2004). Since no systematic information is yet available on these specifi c barriers to healthcare possibly experienced by migrant women in Switzerland, this qualitative study was set up to explore the interaction between migrant women and the healthcare system concerning reproductive health issues, in particular the pregnancy experience in Switzerland.…”
mentioning
confidence: 99%